2014
DOI: 10.3390/molecules19021820
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Prenylated Xanthones from the Pericarps of Garcinia mangostana

Abstract: Bioassay-guided fractionation of an ethanol extract of the pericarps of Garcinia mangostana led to the isolation of two new prenylated xanthones, named 1,3,7-trihydroxy-2-(3-methyl-2-butenyl)-8-(3-hydroxy-3-methylbutyl)-xanthone (1) and 1,3,8-trihydroxy-2-(3-methyl-2-butenyl)-4-(3-hydroxy-3-methylbutanoyl)-xanthone (2), together with the five known compounds garcinones C (3) and D (4), gartanin (5), xanthone I (6), and γ-mangostin (7). Their structures were elucidated primarily based on MS and NMR data. Compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 14 publications
(14 reference statements)
1
23
0
Order By: Relevance
“…The known xanthones were elucidated as garcixanthone A ( 1 ) (Ibrahim, Mohamed, Elfaky, Al Haidari, et al, ), gartanin ( 2 ) (Xu et al, ), normangostin ( 3 ) (Govindachari, Kalyanaraman, Muthukumaraswamy, & Pai, ), and garcinone C ( 4 ) (Sen et al, ; Xu et al, ) on the basis of comparing their spectroscopic data with the literature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The known xanthones were elucidated as garcixanthone A ( 1 ) (Ibrahim, Mohamed, Elfaky, Al Haidari, et al, ), gartanin ( 2 ) (Xu et al, ), normangostin ( 3 ) (Govindachari, Kalyanaraman, Muthukumaraswamy, & Pai, ), and garcinone C ( 4 ) (Sen et al, ; Xu et al, ) on the basis of comparing their spectroscopic data with the literature.…”
Section: Resultsmentioning
confidence: 99%
“…TA B L E 1 NMR spectral data of compound 5 (CD 3 OD, 400 and 100 MHz) The known xanthones were elucidated as garcixanthone A (1) (Ibrahim, Mohamed, Elfaky, Al Haidari, et al, 2018), gartanin (2) (Xu et al, 2014), normangostin (3) (Govindachari, Kalyanaraman, Muthukumaraswamy, & Pai, 1971), and garcinone C (4) (Sen et al, 1982;Xu et al, 2014) on the basis of comparing their spectroscopic data with the literature. Husen et al (2017) reported that G. mangostana improved the streptozotocin (STZ)-induced damage to pancreatic glands and βcells of the islets of Langerhans, through improving the striated muscle cells sensitivity to the insulin decrease and boost the insulin production in diabetic mice (Husen et al, 2017;Nahoum et al, 2000).…”
Section: Characterization Of the Isolated Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pericarps yes [23] 1,4,5,6-Tetrahydroxyxanthone Garcinia bracteata Stem barks yes [24] 1,4-Dimethoxy-2,7-dihydroxyxanthone Cratoxylum cochinchinense Stems no [25] 1,5-Dihydroxy-3-methoxyxanthone-8-O-β-D-Glucopyranoside Swertia paniculata Aerial parts no [26] 1,6,8-Trihydroxy-2,3,4,5-tetramethoxyxanthone Securidaca longepedunculata…”
Section: Garcinia Mangostanamentioning
confidence: 99%